2017
DOI: 10.1111/are.13388
|View full text |Cite
|
Sign up to set email alerts
|

Induction of meiotic gynogenesis in bagrid catfish (Pseudobagrus ussuriensis) with homologous sperm and its confirmation for female homogamety

Abstract: The bagrid catfish, Pseudobagrus ussuriensis, exhibits significant sexual dimorphism in growth rate and body size with males growing faster than females. Therefore, an all‐male culture can dramatically increase the output and profitability of fishery products. According to the monosex breeding route, super‐male individuals’ acquirement by XY male sex reversal and artificial gynogenesis is the key step. An effective protocol to induce meiotic gynogenesis using homologous sperms has been developed in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The experimental data for the three responses are presented in Table . According to Pan et al (), the sex determination mechanism for Ussuri catfish is represented as female homogamety and male heterogamety. The sex ratio for the untreated run (run 6, no MT and AI administered) should be male: female = 1:1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental data for the three responses are presented in Table . According to Pan et al (), the sex determination mechanism for Ussuri catfish is represented as female homogamety and male heterogamety. The sex ratio for the untreated run (run 6, no MT and AI administered) should be male: female = 1:1.…”
Section: Resultsmentioning
confidence: 99%
“…Sex differentiation is completed at the age of 5 months in S. senegalensis , with females differentiating earlier than males (Viñas et al, ). According to Pan et al (), sex differentiation in the Ussuri catfish starts at 21 dph. In our study, MT and the AI were administered at 15 dph.…”
Section: Discussionmentioning
confidence: 98%
“…Although morphology examination has strongly suggested that all adult gynogens inherited from the maternal genome of S. chuatsi with no contribution of the paternal genome from S. scherzeri in this study, further evidence may be needed to exclusively clarify the parentage in the meiotic gynogenesis of mandarin fish. Microsatellite markers have greatly facilitated molecular identification of the gynogenetic offspring in fish, because of their PCR‐based, co‐dominant Mendelian inheritance pattern and highly polymorphic characteristics (Chistiakov, Hellemans, & Volckaert, ; Pan et al, ). Exclusive maternal inheritances have been confirmed in meiotic gynogenetic large‐scale loach (You et al, ), grass carp (Zhang et al, ) and tongue sole (Ji et al, ) by microsatellite makers.…”
Section: Discussionmentioning
confidence: 99%
“…Fertilization rates and hatching rates of the experiment groups of gynogenesis seem of no apparent difference with those of the haploid control group, indicating that spotted mandarin fish is a suitable donor of irradiated heterologous sperm. Mendelian inheritance pattern and highly polymorphic characteristics (Chistiakov, Hellemans, & Volckaert, 2006;Pan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation